Pergeseran Kekuasaan Keluarga Politik di Pilgub Banten 2024: Partai Golkar dan PKS - Imron Wasi (HK Publishing, 2025)
This study discusses the shift in political power from one political elite to another at the local level within the scope of kinship politics. In the 2024 Banten Gubernatorial Election, the two candidates met, Airin Rachmi Diany-Ade Sumardi and Andra Soni-Achmad Dimyati Natakusumah. Airin Rachmi Diany represents the Tubagus Chasan Sochib political family which has dominated political power in Banten, especially since Banten first became a province. This political family has a deep-rooted political entity such as the Golkar Party. As a result, the Golkar Party has never been absent in controlling the executive power of Banten through its cadres who come from the Tubagus Chasan Sochib political family. Meanwhile, Achmad Dimyati Natakusumah has a political territory in Pandeglang Regency, which until now is still in the arena of kinship politics. The research method used is library research such as journals, books, research reports, and relevant research reports (Zed 2004). This study also uses a theoretical approach to answer the research questions, including the theory of power elites (Mills 1956). The result is a shift in political elites from the Tubagus Chasan Sochib political family (incumbent) to other political elites such as Achmad Dimyati Natakusumah, because the Tubagus Chasan Sochib political family (incumbent) failed to use control restrictions by parochializing power or party contracting. This is because the construction of a large coalition was actually built by the candidate pair Andra Soni-Dimyati Natakusumah. In fact, in previous gubernatorial elections, the Tubagus Chasan Sochib political family was always supported by political parties with large coalitions, including the Gerindra Party. Then, Andra Soni-Dimyati Natakusumah (opposition) managed to take advantage of this weakness by opening boundaries by inviting the presence of national elites in the 2024 Banten gubernatorial election, and the development of opinions created by Andra Soni-Dimyati Natakusumah which succeeded in influencing voter preferences, especially regarding 'Banten Anti-Corruption'. Keywords: Power Shift, Power Elite, 2024 Banten Gubernatorial Election, Golkar, PKS.